INFLUENCES OF PUBLIC BICYCLE ON URBAN PUBLIC TRANSPORT： A STUDY ON HANGZHOU CITY, CHINA - C. B. Wang; K. Hokao; L. Gao (International Association of Lowland Technology, 2011)
With the rapid progress of urbanization, urban transportation problem has become a bottleneck that limits sustainable urban development all over the world. The promotion of urban public bicycle provides a new way for the city government to achieve the goal of public-transport-prior strategy and thus solve traffic problem to some extent. The paper took Hangzhou city as an example to discuss the existing problems, and then based on the analysis of urban bicycle role, proposed some measures to optimize the development of urban public transport system.